A two-waved representation of the solutions of differential equations describing the dynamics of some constructions with variable load - Goroshko, O. A.; Горошко, О. А.; Dem'yanenko, Anatoliy; Дем'яненко, Анатолій Григорович (Springer Link, 1974)
The integration of the equation leads to the problem of the transverse oscillations of beams lying on an elastic foundation, the problem of the axially symmetric oscillations Інтегрування рівняння призводить до задачі про поперечні коливання балок, що лежать на пружній основі, задачі про осесиметричні коливання.
Двохвильове представлення розв'язків диференціальних рівнянь, що описують динаміку деяких конструкцій зі змінним навантаженням
Keywords: differential level; диференціальне рівняння; variable load; змінне навантаження; axisymmetric oscillations; осесиметричні коливання